Prevalence of geriatric syndromes in persons over 65 years: the first results of the EVCALIPT study - O. N. Tkacheva; N. M. Vorob’eva; Yu. V. Kotovskaya; O. D. Ostroumova; M. S. Chernyaeva; M. V. Silyutina; A. V. Chernov; S. G. Testova; L. N. Ovcharova; E. V. Selezneva (Российский кардиологический журнал)
Aim. To study the prevalence of geriatric syndromes and assess their relationship with senile asthenia in persons aged ³65 years living in Russian regions with different demographic, climatic and socio-economic characteristics.Material and methods. We examined 664 patients aged 65-107 years (mean age, 79±9 years; men, 25%) living in Moscow (n=365) and Voronezh (n=299). All patients underwent a comprehensive geriatric examination, which consisted of two stages: a survey with original questionnaire and an objective examination.Results. The prevalence of senile asthenia was 66,4%, including 47,4% in people aged 65-74, 71,1% — 75-84 years, and 82,8% — ³85 years (p for trend <0,001). Senile asthenia was associated with age (odds ratio (OR), 2,36; 95% confidence interval (CI), 1,89-2,93; p<0,001) and female sex (OR, 1,52; 95% CI 1,06-2,18; p=0,024). Patients with senile asthenia had a lower socioeconomic status. Also, close associations of senile asthenia with other geriatric syndromes (dementia, depression, vision and hearing impairment, incontinence, falls, high risk of falls, functional decline, failure to thrive) with OR from 1,32 to 7,22 were revealed.Conclusion. The first results of the EVCALIPT study indicate a high incidence of senile asthenia in persons aged ³65 years and its close association with other geriatric syndromes and socio-economic factors.